Urinary concentrations of phthalate metabolites, bisphenols and personal care product chemical biomarkers in pregnant women in Israel. (July 2018) - Machtinger, Ronit; Berman, Tamar; Adir, Michal; Mansur, Abdallah; Baccarelli, Andrea A.; Racowsky, Catherine; Calafat, Antonia M.; Hauser, Russ; Nahum, Ravit
Abstract: Mounting evidence suggests possible adverse effects of intrauterine exposure to certain phenols and phthalates, two classes of endocrine disruptor chemicals, on the developing fetus, with consequences into later life. These findings have contributed to the replacement of some chemicals, such as di‑2‑ethylhexyl phthalate (DEHP) and bisphenol A (BPA), in consumer products. For the current study we quantified urinary concentrations of biomarkers of exposure among 50 pregnant women in Israel to several phthalates, bisphenols and personal care product chemicals, as well as DEHP and BPA alternatives. We detected 14 of the 31 biomarkers in more than 90% of the women. We detected biomarkers of 1, 2‑cyclohexane dicarboxylic acid, diisononyl ester (DINCH), bisphenol S, and bisphenol F not as frequently (27–56%). This study is the first to evaluate exposure to triclosan, bisphenols, parabens, and phthalates and BPA alternatives among Israeli pregnant women. Highlights: Pregnant women in Israel are exposed to phthalates and phenols. Detection frequencies of biomarkers of phthalate alternatives and bisphenol A substitutes ranged from 27–56%. Urinary concentrations of most phthalate and phenol metabolites in Israel were similar or lower compared with those from women in the U.S. NHANES.